EVALUATION OF MODIFIED CONGO RED AGAR FOR DETECTION OF BIOFILM PRODUCING MDR KLEBSIELLA PNEUMONAIE CLINICAL ISOLATES - Zinah Makki Al-yozbakee; Khalid Omar Mohammad (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The notoriety of Multiple Drug Resistant (MDR) K. pneumoniae extends beyond nosocomial or community acquired infections, since it is a major cause of biofilm-related infections. The utilization of a very specific or distinct media, Congo Red Agar (CRA), for detection of biofilm, has significant drawbacks, including inconsistencies in the creation of black pigment. In this study, an assessment of Modified Congo Red Agar (MCRA), for detection of biofilm, was performed on 23 multidrug-resistant (MDR) K. pneumoniae strains obtained from various clinical samples. The aim of this study was to assess the effectiveness and dependability of Modified Congo Red Agar (MCRA) as an alternative medium for studying biofilm production to the non modified Congo Red Agar. Also to examine the prevalence of the fimH gene, which is necessary for biofilm formation among these isolates. Lastly to determine the relationship between antibiotic resistance, the presence of the fimH gene, and the ability to produce biofilm among K. pneumonaie strains. These strains were diagnosed according to their specific bacteriological characteristics. After assessing antibiotic susceptibility, all MDR K. pneumoniae isolates exhibited the presence of the fimH gene using the PCR method. On CRA 20 isolates were strong biofilm producer as they appeared as black colored colonies, two were moderate biofilm producer (pink colored) and only 1 was non biofilm producer ( red colored) colony. On MCR the same results for biofilm production to CRA, except for one colony differed as it appeared red (non biofilm producer) on MCRA and pink (moderate biofilm producer) on CRA. However, the growth of 75% blackness pigment of MDR K. pneumoniae strains on the CRA decreased over time. The phenotypic pigmentation on CRA was enhanced by modifying the contents of the agar that led to the persistent development of a highly concentrated black pigment in isolates containing the fimH gene for 2 to 4 days, with no drop in pigmentation seen over time. The change of the agar ingredient enabled the stable synthesis of black pigment and also resulted in a reduction in the cost of agar preparation. Key Words: Biofilm, Congo Red Agar, fimH gene, Modified Congo Red Agar, MDR K. pneumonaie.